2015
DOI: 10.1111/aos.12811
|View full text |Cite
|
Sign up to set email alerts
|

Lamellar changes in the keratoconic cornea

Abstract: ABSTRACT.Purpose: The purpose of this study was to identify ultrastructural changes associated with ectasia and to determine the association between lamellar count and corneal thinning. Methods: Five surgically removed keratoconic corneal buttons and four, nonkeratoconic, normal eye bank control corneas were processed for transmission electron microscopy using an established protocol, ensuring minimal tissue distortion. A sequence of overlapping digital images, spanning the full apical cone corneal thickness, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 27 publications
1
24
0
1
Order By: Relevance
“…The latest ultrastructural analysis of keratoconic corneal buttons, using transmission electron microscopy, suggested that KTCN is associated with the splitting of existing collagen lamellae into smaller units, which results in a higher total lamellar count. 37 The mechanism of lamellar alteration in KTCN stroma is not fully understood. However, several studies have indicated that collagen slippage observed in KTCN corneas may be due to a loss of cohesion between collagen fibrils and other ECM components.…”
Section: Discussionmentioning
confidence: 99%
“…The latest ultrastructural analysis of keratoconic corneal buttons, using transmission electron microscopy, suggested that KTCN is associated with the splitting of existing collagen lamellae into smaller units, which results in a higher total lamellar count. 37 The mechanism of lamellar alteration in KTCN stroma is not fully understood. However, several studies have indicated that collagen slippage observed in KTCN corneas may be due to a loss of cohesion between collagen fibrils and other ECM components.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies suggest that thinning of the KC cornea might be occurring due to a defect of collagen lamellae formation (Chen et al, 2015; Mathew et al, 2015; White et al, 2017). The different distribution of stromal lamellae in KC compared to normal corneas has been suggested as a precursor for corneal thinning and KC development (Khaled et al, 2017).…”
Section: Pathobiology Of Keratoconusmentioning
confidence: 99%
“…In the normal cornea, the anterior stroma is believed to be biomechanically stronger than the posterior stroma due to a high degree of lamellar interweaving (Komai and Ushiki, 1991, Morishige et al., 2006); however, numerous studies have shown that lamellar interweaving is significantly reduced in the anterior stroma of keratoconus corneas, as well as a loss of collagen lamellae inserting into Bowman's layer (Mathew et al., 2015, Morishige et al., 2007, Morishige et al., 2014, Radner et al., 1998a), ultimately facilitating lamellar “slippage” (Meek et al., 2005). The central anterior cornea is a weak area in keratoconus, forming the apex of the cone, and likely in need of additional biomechanical strength to that provided by collagen.…”
Section: Discussionmentioning
confidence: 99%